Ekstraksi dan Identifikasi Senyawa Antimikroba Herba Meniran (Phyllanthus niruri L.) - WIBOWO MANGUNWARDOYO; ENI CAHYANINGSIH; TEPY USIA (Fakultas Farmasi Universitas Pancasila, 2009)
Phyllanthus niruri L. herbs was extracted using ethanol 96%, ethylacetate and n-hexane. The rendements were respectively 49.25% (for ethanol extract), 4.18% (ethylacetate extract) and0.78% (n-hexane extract). Identification of the ethanol extract using phytochemical assays resulted in alkaloid, flavonoid, saponin, and tannin compounds. Purification of the ethanol extract using thin layer chromatography (TLC) with n-hexane-ethylacetate (6:4) followed by the inhibitory activity test using bioautography TLC showed that the spot of Rf 0,46 inhibited Staphylococcus aureus and that of Rf 0,66 inhibited Candida albicans. Analysis with infra red spectrophotometer showed that the ethanol extract has hydroxyl (-OH) and carbonyl (C=O) functional groups.